Crosslinguistic Interference in Simultaneous Acquisition of Turkish and Italian - Ergün, Anna Lia Proietti (Open Linguistics, 2020)
This study compared the acceptability judgment task (AJT) and translation task (TT) in 10 simultaneous Turkish–Italian bilinguals with age-matched Turkish and Italian monolinguals as a control group. The position of subjects occurring with unaccusative verbs was investigated as the linguistic property. The results of the AJT in Turkish revealed no significant difference between the groups. However, in the Italian AJT, high variability was found in the younger bilinguals. Only bilinguals could participate in the TT. The participants, while translating into Turkish, always produced pragmatically appropriate sentences. In the case of translation to Italian, a significant effect correlated with the position of the subject in the Turkish stimulus was found.